A new configuration design of thermoelectric cooler driven by thermoelectric generator. (September 2019) - Lin, Lin; Zhang, Yu-Feng; Liu, Hai-Bo; Meng, Jing-Hui; Chen, Wei-Hsin; Wang, Xiao-Dong
Highlights: A new configuration of self-driven TEG-TEC system is proposed. Two single-stage TEG is used to separately power a two-stage TEC in the new design. Cooling capacity and maximum temperature drop is enhanced greatly by the new design. Abstract: Self-driven thermoelectric cooler-thermoelectric generator (TEC-TEG) systems have recently attracted a great deal of attention. The single-stage and two-stage TEC-TEG systems have been developed and extensively studied. However, a serial electric current configuration between the TEC and TEG leads to a low cooling capacity or/and a small temperature drop across the TEC, and hence seriously restricts applications of TEG-TEC systems. In this work, a new design of combined TEC-TEG systems is proposed, where two single-stage TEGs are employed to separately power the hot stage and cold stage of the TEC. The advantage of the new design lies in the separate electric current configuration. A three-dimensional thermoelectric model is developed to compare the performance of the new and original designs for various thermocouple number ratios and operating conditions. The comparison demonstrates that the new design not only enhances the cooling capacity of the system but also increases the maximum temperature drop across the TEC. For a TEG-TEC system with only 30 couples, the cooling capacity of the new design is enhanced by 75.0% and the maximum temperature drop is elevated by 76.8%, as compared with the original design. The present predictions provide a useful guidance for the design of combined TEG-TEC systems.